Evaluating Information Technology at Libraries and Archives’ Department Using ITIL V3 Domain Service Transition - Ardianto, Wisnhu (International Journal Labs, 2022)
The use of information technology in the government sector is the main tool in providing services to the environment and especially to the community. The Dki Jakarta Provincial Library and Archives Office (DISPUSIP) is a government agency under the local government of DKI Jakarta Province. DISPUSIP has services in accordance with the organization and work procedures stipulated in the regulation of the Governor of DKI Jakarta Province. Information Technology Infrastructure Library (ITIL) version 3 domain service transition is used to determine the transition of service governance management. The use of questionnaires uses the Process Maturity Framework (PMF) as a framework to assess the maturity of each service management process. DISPUSIP has a maturity rate ranging from 41% to 60% in 7 (seven) subdomains, this value represents the maturity level at level 3, which is defined as a level.